Complex Words in Yurii Andruhovych’s Poetic Lexicon: the Semantic and Derivative Aspect (Linguostylistic Studies, 2025)
The article carries out a structural and semantic analysis of complex words in the poetry of Yurii Andruhovych. The relevance of the research is determined by the originality of Yurii Andruhovych's idiostyle and the lack of a comprehensive linguistic analysis of the language of the writer's works. The semantics, derivational structure, and functioning features of complex words in the context of an artistic work are characterized. The study identified numerical groups of compound nouns and adjectives, several complex verbs, and adverbs in the poetry of Yurii Andruhovych. Applying the semantic-grammatical approach, the identified complex nouns were divided into three lexical-grammatical groups: names of persons, nouns with a specific object meaning, and nouns with an abstract meaning. In his works, as the results of the research show, Yurii Andruhovych uses compound nouns to designate persons and their characteristics, as well as the names of objects, plants, and animals. Productive ways of creating identified complex nouns are stem-based and word-combination. The use of abbreviations to designate institutions, organizations, and subjects in the poetry of Yurii Andruhovych is traced.In Yurii Andruhovych's poetry, complex adjectives most often characterize the features of a person, as well as the realities of the environment. Productive ways of creating complex adjectives are stemming and suffixing. The research findings argue that the discovered compound nouns and adjectives are formed according to word-formation models characteristic of the Ukrainian language.As a result of the analysis, individually author-composed nouns and adjectives were found, which testify to the writer's skill and play a significant stylistic role in the text. It was found that complex words in Yuriy Andruhovych's poetic language are stylistically loaded and perform a descriptive, evaluative, and emotionally expressive role. With the help of complex words, the author creates an emotional and expressive saturation of the text.
Keywords: complex word; composition; word formation; base composition; composite; method of creation